Clinical performance of zirconia–ceramic cantilever fixed partial dentures—Longitudinal nine-year results from a prospective, randomized, controlled pilot study. Issue 3 (July 2019) - Bömicke, Wolfgang; Rammelsberg, Peter; Zenthöfer, Andreas; Ohlmann, Brigitte
Abstract: Purpose: The aim of this study was to prospectively compare the clinical performance of veneered zirconia cantilever fixed partial dentures (Z-CFPDs) and metal–ceramic CFPDs (MC-CFPDs) over 9 years of follow-up in terms of survival. Methods: Twenty-one participants were assigned by simple randomization to receive either 1 Z-CFPD ( n  = 11) or 1 MC-CFPD (n = 10). CFPDs were retained by 2 full crowns and replaced a missing premolar or a central or lateral incisor. Modified USPHS (United States Public Health Service) criteria were used to classify material chipping, retention, marginal integrity, secondary caries, and color of the restorations. The satisfaction of the study participants with the esthetics of their restorations was surveyed; pocket probing depths (PPD), plaque index (PI), and gingival index (GI) were also measured. Study groups were compared by use of U tests (continuous variables), or by use of Fisher exact probability tests (categorical variables) with α  = 0.05. Results: Sixteen participants (n = 8 with a Z-CFPD and n = 8 with an MC-CFPD) attended the 9-year follow-up examination (response rate: 76.2%). Over the 9-year study period, survival of 50% for Z-CFPDs and 75% for MC-CFPDs was recorded ( p  = 0.608). No framework fractures occurred, and no statistically significant differences were observed between the groups regarding changes in PPD, PI, GI, or participant satisfaction ( p >  0.05). USPHS criteria revealed statistically significantly poorer marginal quality for Z-CFPDs than for MC-CFPDs ( p  = 0.009). Conclusion: Within the limitations of this study, Z and MC-CFPDs demonstrated no statistically significant difference in terms of survival.